Solution for nonlinear Riccati equation by block method - Rasedee A.F.N.; Ijam H.M.; Sathar M.H.A.; Ishak N.; Hamzah S.R.; Mus'ab Sahrim; Ismail I. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS